Evaluating the Implementation and Active Living Impacts of a State Government Planning Policy Designed to Create Walkable Neighborhoods in Perth, Western Australia - Hooper, Paula; Giles-Corti, Billie; Knuiman, Matthew (American journal of health promotion, 2014)
Purpose. Evaluate the implementation of a government planning policy (Liveable Neighbourhoods Guidelines) and its impacts on residents' walking behaviors. Design. Cross-sectional study of participants from the RESIDential Environments project (RESIDE). Setting. Nineteen “liveable” and 17 “conventionally designed” housing developments across Perth, Western Australia. Subjects. Five hundred ninety-four participants from RESIDE who resided in 36 housing developments. Measures. Developed in geographic information systems to assess the on-ground implementation of 43 policy requirements. Policy compliance was defined as the degree to which construction of the developments adhered to the standards outlined. Walking behaviors were measured using the Neighborhood Physical Activity Questionnaire. K-means cluster analyses identified groups of homogeneous developments with respect to policy implementation. Analysis. Logistic regression with generalized estimating equations estimated the odds ratios (ORs) and 95% confidence intervals (95% CIs) for the likelihood of undertaking any and ≥ 60 minutes of transport and recreational walking associated with (1) policy compliance and (2) different clusters of developments. Results. There were few significant differences in on-ground outcomes between the two development types. Despite incomplete implementation, the odds of walking for transport increased with overall levels of policy compliance (OR= 1.53, 95% CI 1.13–2.08) and compliance with the community design (OR = 1.3, 95% CI 1.13–1.42), movement network (OR = 2.49, 95% CI 1.38–4.50), and lot layout elements (OR = 1.26, 95% CI 1.06–1.50). Conclusion. Consistent with the aims of the policy, residents in walkable (i.e., liveable) neighborhoods may be more physically active.